New Porous High Surface Area, TiO2 Anatase/SAPO‐35 Mild Brønsted Acidic Nanocomposite: Synthesis, Characterization and Studies on it's Enhanced Photocatalytic Activity. Issue 31 (19th August 2019) - Siliveri, Suresh; Chirra, Suman; Tyagi, Chinkit; Gandamalla, Ambedkar; Adepu, Ajay Kumar; Goskula, Srinath; Gujjula, Sripal Reddy; Venkatathri, Narayanan
Abstract: Anatase TiO2 and Levyne type microporous silico alumino phosphate SAPO‐35 are synthesized by using hydrothermal method. TiO2 /SAPO‐35 nanocomposites were prepared by sol‐gel method with different weight ratios. The synthesized materials were characterized by various analytical techniques such as PXRD, SEM/EDAX, TG/DTA, BET‐Surface area, FT‐IR, UV‐Vis, XPS, MAS‐NMR and photocatalytic study. From PXRD results it clearly evidenced that, the TiO2 anatase peaks and SAPO‐35 combined peaks are in the composite. The spherical shaped TiO2 nanoparticles were found to be dispersed over the rhombohedral SAPO‐35 particles, which was analysed by SEM. BET‐surface area analysis revealed that, the calcined SAPO‐35 has the surface area of 448 m 2 /g, was decreased to 222 m 2 /g for composite which is due to the presence of TiO2 particles having surface area of 85 m 2 /g on the surface of SAPO‐35. The oxidation state and co‐ordination of various elements present in nanocomposite was composed by X‐ray photoelectron spectroscopy. MAS‐NMR analysis has shown that SAPO‐35 has tetrahedral Al, P and Si oxides. Eventhough Al is unique Si and P are in two different environment namely one in S6R and another in D6R with double intensity. The photocatalytic performance of methylene blue degradation under sunlight radiation by the synthesized TiO2 /SAPO‐35 was analyzed. The TiO2 /SAPO‐35 composites degrade the methylene blue under sunlight irradiation in 25 minutes against 90 minuts for pure TiO2 anatase. A plausible mechanism on photocatalytic activity is also proposed. Abstract : In the present work, we have reported the synthesis of a novel anatase TiO2 /Mild Brønsted acidic SAPO‐35 composites through sol‐gel method. The pure and composite materials are characterized in detail. The photocatalytic activity of these materials over methylene blue degradation shows that, the composites are having higher activity than the pure components under Visible light irradiation. The enhanced photocatalytic activity of the composite materials are due to synergistic relation between anatase TiO2 and mild Brønsted acidic SAPO‐35.